Improving Student Learning Outcomes in Islamic Education Learning at SMP Satu Atap Reudeup through the Application of the Problem Based Learning Model - Sahirina; Iswandi (Journal of Action Research in Islamic Education, 2025)
This study aims to improve student learning outcomes in Islamic Religious Education and Character Education (PAI-BP) at SMP Satu Atap Reudeup through the application of the Problem Based Learning (PBL) learning model. The background of this study is the problem of low student learning outcomes indicated by only a small number of students achieving the Minimum Completion Criteria (KKM). The PBL model was chosen because it emphasizes active student involvement in solving real problems, critical thinking, and working together in groups, so it is expected to increase motivation and conceptual understanding. This study is a Classroom Action Research (CAR) carried out in several cycles with the stages of planning, implementation, observation, and reflection. The subjects of the study were grade VII students of SMP Satu Atap Reudeup. Data were collected through learning outcome tests, student activity observation sheets, and documentation, then analyzed descriptively. The results showed an increase in student activeness during learning and an increase in learning outcomes from the pre-cycle to the final cycle, so that the application of the PBL model was proven effective in improving student learning outcomes in the PAI-BP subject. Thus, the Problem Based Learning model can be used as an alternative innovative learning strategy to improve the quality of PAI-BP learning in junior high schools.